KONSEP MEDIA BELAJAR DAN TEORI PEMBELAJARAN BERBASIS TEKNOLOGI - Achmad Mu'afi As'ad; Aziz Abdullah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2022)
Organized learning system is a combination that includes elements of human, material, facilities, equipment, and procedures that interact to achieve a goal. Human element in the system of learning is students, teachers / faculty, librarians, laboratory, administrative personnel as well as those that support the success of the learning process. Information and communication technology is the result of human engineering to information process and the process of delivering a message (ideas, ideas) from one party to another resulting in faster, wider distribution, and longer storage. To be able to take advantage of ICT to improve the quality of learning, there are three things that must be realized that (1) students and teachers should have access to digital technology and the Internet in the classroom, school, and teacher education institutions, (2) must be available the material quality, meaningful and cultural support for students and teachers, and (3) the teacher should have knowledge and skills in using tools and digital resources to help students to mencaqpai academic standards. The demands of learning in the future should be open and two-way, diverse, multi-disciplinary and related to the productivity of work "at that moment" and competitive. Information and communication technology cheaply and easily will eliminate the limitations of space and time that had been limiting world of education. Today many impacts that occur as a result of the development of IT in the country. Indeed, the development of IT if addressed in a positive able to have a positive impact if addressed negative and may be adversely affected as well